Servicios web, mensajería y transferencia de archivos en una intranet en el colegio nacional técnico Tosagua provincia de Manabí - Quiroz Cevallos, María Josefa (2013)
The main objective of the present thesis work was implement services web, messages and transfer of files in an intranet in the administrative area of the Technical National School Tosagua of the county of Manabí to improve the communication and to speed up the transfer of information. The services of the intranet foment to the instantaneous communication among the different departments of the institution. For the execution of the services one worked with the methodology SOFTCAL, same that allowed the exact development of the implementation of the intranet by means of sequential processes. It was necessary to gather information that allowed to develop a design of the location of the different net points and the servant. The used software and the configuration of the ip contributed to that the services of the intranet worked correctly and this way communication settled down and that the same one will be speeded up.